2013
DOI: 10.1089/nat.2012.0403
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biodegradable Peptide Carriers for Light-Directed Targeting

Abstract: A promising strategy for increased intracellular delivery of nucleic acids with the benefit for targeting is photochemical internalization (PCI). PCI relies on the use of a photosensitizing compound that photochemically destroys membranes in the endocytic pathway after illumination, resulting in cytosolic transfer of endosomal content. PCI technology combined with biodegradable polyamino acid carriers and nucleic acids delivers effective targeting and improved biosafety. In an in vitro model system, we have ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In the race for biosafety, biocompatibility and biodegradability of drug delivery systems and gene transporters, the polyamino acids family has demonstrated very interesting properties as well as high efficiency, whether modified to acquire or not proton sponge capacity for lysosomal escape [ 63 ]. Jorgensen J.A.L et al showed for the first time the capacity of the unmodified poly-L-arginine, poly-L-histidine or poly-L-lysine to carry and deliver siRNA under PCI mechanism activated by blue light in the presence of TPPS 2a as photosensitizer [ 63 ].…”
Section: Photochemical Internalization (Pci) Mechanismmentioning
confidence: 99%
“…In the race for biosafety, biocompatibility and biodegradability of drug delivery systems and gene transporters, the polyamino acids family has demonstrated very interesting properties as well as high efficiency, whether modified to acquire or not proton sponge capacity for lysosomal escape [ 63 ]. Jorgensen J.A.L et al showed for the first time the capacity of the unmodified poly-L-arginine, poly-L-histidine or poly-L-lysine to carry and deliver siRNA under PCI mechanism activated by blue light in the presence of TPPS 2a as photosensitizer [ 63 ].…”
Section: Photochemical Internalization (Pci) Mechanismmentioning
confidence: 99%
“…Further studies on using PCI for oligonucleotide mediated gene expression silencing have been performed with siRNA in combination with a variety of delivery vehicles. Thus, Bøe and co-workers showed good effects of PCI with siRNA with polymeric vehicles such as polyethylenimine [164], cyclodextrin-containing polymers [165], peptides [166] and polyamidoamine (PAMAM) carriers [167]; as well as with some, but not all of the tested lipid vehicles [164]. In case of PAMAM dendrimer complexed the authors tested several generations (0-7) of PAMAM dendrimers complexated with both a GFP siRNA and a GFP mRNA with regard to their PCI-mediated gene modulation efficiency in OHS-EGFP and OHS osteosarcoma cells respectively.…”
Section: Pci Mediated Oligonucleotide Deliverymentioning
confidence: 99%
“…Polycations can be used for effecting nucleic acid uptake by conferring a positive charge to the negatively charged nucleic acids so that a polycation/nucleic acid complex can be taken up after electrostatic interaction with the negatively charged cell surface. This is a general uptake mechanism that works very well in combination with PCI with many types of nucleic acids ranging from PNAs conjugated to positively charged amino acids [163,217] thorough poly-amino acid mediated delivery of plasmids and mRNA [159,166], to adenovirus coated with polycations [208]. To the extent that the employed polycations are not able to induce a "proton sponge" effect, such systems will often have very low gene delivery efficiency on their own, meaning that PCI can be used to literally turn delivery on, with enhancement factors up to >100 times being observed [85,190].…”
Section: Considerations Regarding the Use Of Pci To Enhance The Theramentioning
confidence: 99%
“…54 A similar approach has also been applied for gene transfection using biodegradable polyamino acid carriers. 55 A nanocarrier based on chitosan bearing a covalently bound porphyrin resulted in successful PCI transfection of EGFP in human colon carcinoma cells in vitro. 56 The same method could be applied for cytotoxic drug delivery.…”
Section: Macromolecular Drug Carriersmentioning
confidence: 99%
“…A synergistic enhancement in cytotoxicity was observed using PCI . A similar approach has also been applied for gene transfection using biodegradable polyamino acid carriers . A nanocarrier based on chitosan bearing a covalently bound porphyrin resulted in successful PCI transfection of EGFP in human colon carcinoma cells in vitro .…”
Section: Cytotoxic Agents Used With Pcimentioning
confidence: 99%